The Effect Of Carrot Juice (Daucus Carota L) On Reduce The Degree Of Dysmenorrhea In Adolescent Women At State High School 1 Sampit, Kotawaringin Timur Regency - Tety Ripursari; Emi Yunita; Titis Putri Antari (Journal of Health Science Community, 2024)
During menstruation women sometimes experience pain, the nature and level of pain varies, depending on each woman's pain threshold. Excessive pain during menstruation is called dysmenorrhea and one of the treatments for dysmenorrhea is non-pharmacological. The purpose of this study was to analyze the effect of Carrot Juice (Daucus Carota L) on reducing the degree of dysmenorrhea pain in adolescent women at State High School 1 Sampit, East Kotawaringin Regency.The research design used was a pre-experimental design method with a pretest-posttest design using a cross-sectional approach. The sample in this study were 46 respondents with purposive sampling. The results of bivariate analysis using the Wilcoxon Test Statistical test with α 0.05.From the results of the study it was found that the majority of respondents experienced controlled severe pain before being given carrot juice, namely as many as 28 respondents (60.9%), Almost all respondents experienced moderate pain after being given carrot juice, namely as many as 36 respondents (78.3%). The results of statistical tests using the Wilcoxon test showed that p value = 0.000 <α (0.05), which means that H0 is rejected, H1 is accepted. means the effect of Carrot Juice (Daucus Carota L) on Reducing the Degree of Dysmenorrhea Pain in adolescent women at State High School 1 Sampit, East Kotawaringin Regency.Provision of carrot juice (Daucus Carota L) is effective for reducing the degree of dysmenorrhoea pain in young women, so it is expected that schools and health workers will provide socialization to overcome dysmenorrhoea pain with non-pharmacological alternatives, namely using carrot juice.